The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1940161220968534
|View full text |Cite
|
Sign up to set email alerts
|

Still Images—Moving People? How Media Images of Protest Issues and Movements Influence Participatory Intentions

Abstract: While media images can ease political information perception and processing, the impact of images on behavioral intentions to engage in protest is relatively unexplored. We ask: Under what conditions can news images of protest “move” people and affect the willingness to participate? Aiming to answer this question from an information-processing perspective, we shed light on the nexus between spontaneous, sensory behavior and cognition in response to news media images of protest. We conducted a multigroup experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
0
6
0
2
Order By: Relevance
“…Answering RQ2, the images were mostly negative, capturing users' attention (Kleinnijenhuis, 2008), and likely to elicit emotions associated with collective action, such as anger (Cohen-Chen & Van Zomeren, 2018;Stürmer & Simon, 2009;Tausch et al, 2011) but also fear and optimism. Prior work has shown that negative (but not positive) images can increase (normative) collective action intention (Geise et al, 2021), while Winter (2018) argues that documenting the victimization and suffering of the ingroup makes the promise of the extremists' utopian vision even more powerful.…”
Section: Main Findings and Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Answering RQ2, the images were mostly negative, capturing users' attention (Kleinnijenhuis, 2008), and likely to elicit emotions associated with collective action, such as anger (Cohen-Chen & Van Zomeren, 2018;Stürmer & Simon, 2009;Tausch et al, 2011) but also fear and optimism. Prior work has shown that negative (but not positive) images can increase (normative) collective action intention (Geise et al, 2021), while Winter (2018) argues that documenting the victimization and suffering of the ingroup makes the promise of the extremists' utopian vision even more powerful.…”
Section: Main Findings and Theoretical Implicationsmentioning
confidence: 99%
“…Both valence and distinct emotions influence collective action. Research on collective action has shown that negative images are not only more attention grabbing but also increase willingness for collective action (Geise et al, 2021). The social identity model of collective action (van Zomeren et al, 2008) postulates that collective action, in general, has three main drivers: First, people must identify with their respective ingroup.…”
Section: Introductionmentioning
confidence: 99%
“…This study extends from scholars across social sciences and humanities who have analyzed Thunberg’s speeches and writings (García 2020; Skilbeck 2020); analyzed social media posts that contain hashtags and keywords relevant to the climate movement (Boulianne et al 2020; Han and Ahn 2020; Jung et al 2020); and examined how mainstream media frames Thunberg’s message and actions (Ryalls and Mazzarella 2021; von Zabern and Tulloch 2021). Visual information has been shown to help people better process and remember information (Graber 1996), and, in the realm of social movements, motivate viewers toward engagement in protests (Geise et al 2021). While this study does not analyze the intentions behind Thunberg’s posts nor the linkages between communication and engagement, it contributes to this research on Thunberg as a globally influential communicator by attending to her own framing and powerful use of visual communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Más allá de que el uso de Twitter con fines políticos difiere enormemente por países (Scherpereel et al, 2016), la pandemia abre la puerta a un redescubrimiento de las potencialidades de las redes sociales, ampliamente abordadas como lugares de emisión y escasa interactividad (Geise et al, 2021). La Covid-19 ha acelerado los cambios en los patrones de consumo, de ahí que pueda haber espacio para aproximaciones más visuales y dinámicas de Twitter que entronquen con los mecanismos de transparencia demandados por la sociedad.…”
Section: Estrategias Y Comunicación Política En Twitterunclassified